An analysis of a closed COPD online health community: identifying information needs and credibility of sources. (15th July 2020) - Boyce, LeAnn; Prybutok, Gayle
Online health communities (OHCs) have witnessed incredible growth over the past few years. Studies have explored communities related to cancer, diabetes, and other chronic diseases. However, few studies, have examined online communities focused on chronic obstructive pulmonary disease (COPD). This study investigates COPD360social.com, an online forum for COPD patients, to answer the following research questions: what health information do forum members need; what health information sources do they prefer, and how credible is the information exchanged on the forum? We found that most of the participants' reasons for posting on this site were to look for emotional support. This study indicates that COPD patients have health information needs and a monitored social health online community that is available to patients 24/7 answers questions that arise at the time of need.